Pemetaan Prioritas Kerja Generasi Z: Studi Komprehensif dan Implikasi Strategis Manajemen Kantor di Era AI - Syafani, Rheina Syahla; Hasya, Nazwa Nur; Chaniago, Harmon (Asosiasi Ahli Administrasi Indonesia, 2025)
This study is important because understanding the work preferences of Generation Z is crucial for organizations to attract and retain young talent in the digital era. The research aims to identify the key factors influencing Generation Z’s choice of workplace and their expectations regarding a modern work environment. Employing a qualitative approach, data were collected through in-depth interviews with 12 Generation Z informants and were analyzed thematically. The findings reveal that Generation Z prioritizes financial stability through fixed salaries, flexibility in work time and location, a supportive work atmosphere, and career development opportunities. Additionally, they value the integration of technology, particularly artificial intelligence, as a means to enhance work efficiency, while emphasizing the need for a balance between technological and human roles. Collaborative leadership styles, constructive feedback, transparency, and autonomy are also among their primary expectations from management. The implications of this study suggest that management should adapt recruitment and retention strategies by offering competitive compensation, work flexibility, a positive work environment, and opportunities for personal growth to create an attractive workplace for Generation Z.